Phytochemical And Pharmacological Studies Of Ethanol Extract Of Dalbergia Sissoo Seeds: An Approach For The In-Vivo Analgesic And Antipyretic Activities - MALLINATH H. HUGAR,; KALLAPPA M. HOSAMANI,; MD. LIYAKATH AHMED\, (International Journal of Pharma and Bio Sciences, 2010)
In the course of search for the biological active constituents present in the alcoholic extract of Dalbergia sissoo seeds (Shisham or Sisam).The peripheral analgesic activity of Sisam seed extract (SSE) was studied using acetic acid-induced writhing in mice and by Randall-Selitto assay in rats. Further, the central analgesic activity of SSE was studied by tail-clip test and hot plate method in mice. The antipyretic activity of SSE was studied in Brewer’s yeast-induced pyrexia in rats. Results showed significant decreased writhing movements in mice by acetic acid-induced writhing test and significant increased in the pain threshold capacity in rats in Randall-Selitto assay and the reaction time in hot-plate test but not in tail-clip test for analgesic activity. Moreover, it also showed significant antipyretic activity in Brewer’s yeast-induced pyrexia in rats throughout the observation period of 6 h. Thus, SSE has moderate analgesic and remarkable antipyretic activities.